(untitled) (Medico Legal Update, 2021)
Background: Use of sensors for assessment and treating orthopedic and neurological conditions in physical therapy and rehabilitation is in practice since last 2 decades. Its efficiency has been promising with advancements in research and clinical practice. Objective: The aim of the present review is to synthesize and evaluate studies which have performed a role to test efficacy of sensors following orthopedic and neurological conditions for research and clinical practice in physical therapy and rehabilitation. Data Source: Are view of articles identified from high impact journal from Springer, Hindawi, MDPI, PLOSone, De Gruyter was performed by both researchers. Study Eligibility Criteria: Articles published only in English between January, 2010 and December, 2019 were included which investigated role of sensors in physical therapy and rehabilitation. Study Appraisal and Synthesis Method: Studies were grouped as wearable, bio-mechanical pressure, motion capture sensing technology and stretch sensors. Results: From the 17 articles identified, 10 papers were involved in the review which was deemed as being of high quality. Conclusion: Sensor technology is a full-fledged and rapidly growing field with imperative focus and noteworthy role in assessment and treatment for upper and lower limbs insufficiencies, spinal curve corrections in numerous orthopedic and neurological conditions. Research over the past 10 years grandly focused on the use of sensors in physical therapy and rehabilitation.